The infiltrator - Hendricks, T. R. (Hendricks, T. R. Derek Harrington novel, 2024)
One year after the clash with his former students in upstate New York, retired Marine Warrant Officer and SERE instructor Derek Harrington is the tip of the FBI's spear in their mission to eradicate the domestic terrorist group known as Autumn's Tithe. After several successful operations, intelligence points to one final camp in the remote Kentucky wilderness, and Derek prepares to take down Autumn's Tithe for good. At the same time ex-FBI Special Agent Hannah Kittle, or Sarah as she is known to the group, devises a plan to meet Derek and her one-time Bureau colleagues head on. Yet her benefactor's faith in Sarah's ability to lead Autumn's Tithe is waning, and other plans are being enacted. Knowing full well what it means for her should those plans succeed where she has failed, Sarah will stop at nothing to see that she is the victor. As the competing agendas unravel, events place Derek and Sarah on a collision course, setting the stage for a confrontation that will bring Autumn's Tithe right to Derek's doorstep. --